Industrialization’s eye view on theranostic nanomedicine - Sivasubramanian, Maharajan; Lin, Li-Jie; Wang, Yu-Chao; Yang, Chung-Shi; Lo, Leu-Wei (Frontiers in Chemistry, 2022)
The emergence of nanomedicines (NMs) in the healthcare industry will bring about groundbreaking improvements to the current therapeutic and diagnostic scenario. However, only a few NMs have been developed into clinical applications due to a lack of regulatory experience with them. In this article, we introduce the types of NM that have the potential for clinical translation, including theranostics, multistep NMs, multitherapy NMs, and nanoclusters. We then present the clinical translational challenges associated with NM from the pharmaceutical industry’s perspective, such as NMs’ intrinsic physiochemical properties, safety, scale-up, lack of regulatory experience and standard characterization methods, and cost-effectiveness compared with their traditional counterparts. Overall, NMs face a difficult task to overcome these challenges for their transition from bench to clinical use.